EVALUASI MUTU BENIH BEBERAPA VARIETAS PADI (Oryza sativa L.) YANG DIPASARKAN MELALUI E-COMMERCE - Sustia Dewi, Ni Kadek Ema; Azizah Ridha Ulilalbab; Nabila Maharani; Bias Denasa (UNIVERSITAS PEMBANGUNAN NASIONAL ”VETERAN” YOGYAKARTA, 2025)
Rice (Oryza sativa L.) is the main staple food commodity in Indonesia. This study aimed to evaluate the seed quality of several local rice varieties obtained from e-commerce, based on standard seed quality parameters. The experiment was conducted using a Completely Randomized Design (CRD) with a single factor consisting of five local rice varieties: Rojolele, Sedayu, Mentik Susu, Ketonggo, and Jeliteng. Each treatment was replicated four times, resulting in 20 experimental units. The assessed parameters comprised seed moisture content,vigor index, germination percentage, maximum growth potential, pure seed content, proportion of other crop seeds, inert matter content, and seed health (pathology) assessment. The results showed that the Ketonggo variety had the lowest moisture content and the highest germination rate, vigor index, and maximum growth potential. The Mentik Susu variety exhibited the highest percentage of pure seeds and the lowest percentages of other crop seeds and inert matter. The was non-compliant with the established genetic quality standards with a pure seed percentage of less than 98%. Three types of fungi were identified using the blotter test method, namely Aspergillus niger, Aspergillus flavus, and Alternaria sp.